Characterization of the complete mitochondrial genome of Plagiorchis maculosus (Digenea, Plagiorchiidae), Representative of a taxonomically complex digenean family. (August 2019) - Suleman,; Ma, Jun; Khan, Mian Sayed; Tkach, Vasyl V.; Muhammad, Nehaz; Zhang, Dong; Zhu, Xing-Quan
Abstract: Despite the highly divergent morphology, pathogenicity and worldwide distribution of digenean parasites belonging to one of the largest families, the Plagiorchiidae, there are no complete mitochondrial (mt) genomes published to date for plagiorchiids. In this study, we obtained nuclear ribosomal DNA (ITS region and 28S rDNA) sequences and the complete mt genome sequences of Plagiorchis maculosus (Rudolphi 1802) Braun, 1902, and assessed its phylogenetic relationship with other xiphidiates, based on the mtDNA sequences. The obtained ITS and 28S rDNA sequences were identical to the corresponding sequences of P. maculosus available in GenBank. The complete mitochondrial genome of P. maculosus (14, 124 bp) contained 36 genes ( atp 8 is absent) and a long non-coding region (NCR) with two sets of repeated sequences of 283 nucleotides each. The phylogenetic tree resulting from Bayesian inference (BI) analyses based on concatenated nucleotide sequences of all 36 genes of P. maculosus and other xiphidiates mitochondrial genomes, indicated that P. maculosus (and the Plagiorchiidae) is phylogenetically closest to the Brachycladiidae and Paragonimidae. The present study describes the first mitochondrial genome from the type genus of the family Plagiorchiidae. The overall gene arrangement, nucleotide composition, A + T contents, AT and GC skew and codon usage with relative synonymous codon usage (RSCU) for 12 PCGs are described. Characterization of mitochondrial genomes from additional plagiorchiid taxa is necessary to make further progress in phylogenetic and epidemiological studies of these digeneans as well as accurate diagnostics of these parasites including those parasitic in humans. Graphical abstract: Unlabelled Image Highlights: The entire mt genome of Plagiorchis maculosus is 14, 217 bp in length. The P. maculosus mt genome contains the standard 36 flatworm mitochondrial genes. The AT content is the highest among the published Xiphidiatan mt genomes. Plagiorchiidae is phylogenetically closest to the Brachycladiidae and Paragonimidae. The mt genome of P. maculosus providing novel genetic markers for systematic studies